Common Fixed Point Theorems for Mappings Satisfying implicit Relation in Bipolar metric Space} (European Journal of Pure and Applied Mathematics, 2025)
In this article, we introduce the concept of compatible mappings of type $(A)$ and weaken the same in the setting of Bipolar metric spaces and established fixed point results in the setting of Bipolar metric spaces, using implicit relation function. The derived results have been supplemented with suitable non-trivial examples. Our results have extended and generalized some results proven in the past and some open problems for future research has been given.